2017
DOI: 10.1002/cpp.2103
|View full text |Cite
|
Sign up to set email alerts
|

In‐session behaviours and adolescents' self‐concept and loneliness: A psychodrama process–outcome study

Abstract: As adolescents spend many hours a day in school, it is crucial to examine the ways in which therapeutic practices in schools promote their well-being. This longitudinal pilot study examined the contribution of school-based psychodrama group therapy to the self-concept dimensions and perceived loneliness of 40 Israeli adolescents (aged 13-16, 60% boys) in public middle schools. From a process-outcome perspective, we also examined the understudied trajectory of adolescents' in-session behaviours (process variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…This study included three groups and compared the effects of group PD with anti-depressant medication to the effects of a group with antidepressant medication alone and to a healthy control group of volunteers with similar ages and education levels. The second study involved adolescents at risk that was conducted at a middle school in Israel [45]. This study included two groups and compared the effects of group PD to a waiting list control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included three groups and compared the effects of group PD with anti-depressant medication to the effects of a group with antidepressant medication alone and to a healthy control group of volunteers with similar ages and education levels. The second study involved adolescents at risk that was conducted at a middle school in Israel [45]. This study included two groups and compared the effects of group PD to a waiting list control group.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the treatment, the study at the university polyclinic had a loosely structured treatment with a session duration of three hours per week, for 16 sessions [19]. The study at the school did not follow a treatment protocol, and session duration was 1.5 hours per week for 16 to 20 sessions [45]. In both studies, information concerning the qualification of the therapists was provided and both studies indicated that the therapist was given clinical supervision during treatment implementation.…”
Section: Resultsmentioning
confidence: 99%
“…The current study contributes to our understanding of the potential of psychodrama group therapy in dealing with the distress and isolation of acute psychiatric inpatients. Current literature describes how the unique features of psychodrama therapy are useful in fostering spontaneity and creativity ( Farmer, 1995 ; Roine, 1997 ; Blatner, 2000 ; Schacht, 2007 ), and in treating particularly difficult populations where traditional psychotherapy is limited ( Karp, 1994 ; Vieira and Risques, 2007 ; Karatas, 2011 ; Orkibi et al, 2017 ). The unique contribution of this study is the intimate encounter that it provides to researchers and practitioners through holistic and naturalistic, in-depth investigation in a real-life setting, with manifestations of the distress accompanying psychiatric hospitalization, the processes that take place within an inpatients therapy group, and with therapeutic dimensions such as psychodramatic sharing, which are rarely dealt with by the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…The psychodramatic stage allows individuals to approach their feelings and thoughts in situations where the verbal dialog of analytic psychotherapy is limited ( Farmer, 1995 ). Psychodrama group therapy is especially beneficial for evoking spontaneity and uncovering creativity in emotional distress cases ( Holmes and Karp, 1991 ; Roine, 1997 ; Blatner, 2000 ; Schacht, 2007 ; McVea et al, 2011 ) and in treating difficult populations, such as at-risk adolescents, alcoholics, drug addicts, sexual offenders, and those coping with anorexia ( Karatas, 2011 ; Karp, 1994 ; Hollander and Craig, 2013 ; Orkibi et al, 2017 ). Another advantage of psychodrama is its effectiveness in treating a wide range of psychopathologies, including depression, anxiety disorders, obsessive compulsive disorder, post-traumatic stress disorder, and other related phenomena such as self-stigma in people coping with mental illness ( Vieira and Risques, 2007 ; Belil, 2010 ; Gatta et al, 2010 ; Orkibi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is probably due to this association that the study of psychodrama’s effectiveness, in a controlled and more rigid academic way, has been neglected.” Nevertheless, the discovery of the therapeutic potency of spontaneity ( Moreno, 2010 ) and its effect on developing human interactions has been central to the process of recognizing the importance of psychodrama. The relevance of our study is directly linked to the discussion of the effects of psychodrama in several different contexts of application, clinical and non-clinical ( Kipper, 1978 ; D’Amato and Dean, 1988 ; Kipper and Hundal, 2003 ; Orkibi et al, 2017a , b ; Azoulay and Orkibi, 2018 ; Testoni et al, 2018 ) and to the need for solid methodologies that gather mixed approaches and acknowledge the complexity of this type of intervention, not always easily amenable to empirical research ( Kim, 2003 ). All in all, as stated by Kipper and Ritchie (2003 , p. 23) in their meta-analysis about the effectiveness of psychodramatic techniques, “the findings appear to shed a positive light on the issue of the validity of psychodramatic interventions and to encourage research regarding the specific psychotherapeutic effects of its basic techniques.”…”
Section: Introductionmentioning
confidence: 99%